2020
DOI: 10.46542/pe.2020.202.124135
|View full text |Cite
|
Sign up to set email alerts
|

Using in silico process simulation tools in pharmacy education: Considerations for pivoting to online learning

Abstract: The COVID-19 pandemic has required identification of pharmaceutical learning content and teaching methods which can support attainment of learning outcomes through online delivery. In silico, or computer based, process simulations are ideal tools for incorporation into online programme elements, however the scaffolding of learning with in silico tools requires a structured approach. A previously developed face-to-face workshop, which used in vitro and in silico dissolution testing, was pivoted to an online lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Following the research findings of [14], it was shown that both suggested delivery and assessment were adequate to asynchronous and synchronous learning frameworks.…”
Section: Modell and Simulation In Pharmacy Educationmentioning
confidence: 92%
“…Following the research findings of [14], it was shown that both suggested delivery and assessment were adequate to asynchronous and synchronous learning frameworks.…”
Section: Modell and Simulation In Pharmacy Educationmentioning
confidence: 92%
“…Una iniciativa reciente llamada modelamientos in silico son parte de los laboratorios virtuales que permiten simular procesos biológicos experimentales haciendo uso de softwares, programas bioinformáticos y recursos computacionales (D'Arcy et al, 2020). Respecto a la utilidad de los modelamientos in silico en la educación superior durante el período de crisis por la pandemia COVID-19, fue una gran alternativa de enseñanza.…”
Section: Introductionunclassified